Revisiting the Role of Common Labeling in a Context of Asymmetric Information: Critique and Extensions - Tomas Nilsson; Paul Preckel; Bo Öhlmer; Hans Andersson (European Regional Science Association (ERSA), 2003)
Households in the Western Hemisphere are no longer self sufficient in food production. Viewing the product from the shelves in the grocery store makes it difficult for the consumer to gain insight in the production practices and the quality attributes to the product. Formally, we can describe this as the food products purchased from a grocery store contain less search characteristic. Thus, the consumer cannot determine the quality of the product before the purchase. Instead the food products are characterized to be more of experience (quality is revealed after purchase) or credence characteristic (quality is not revealed even after purchase). Although it is not possible to determine the quality of the packaged food product on the shelves, the issues concerning food product quality are not trivial issues in society. The consumers may boycott not only food that can contain food-borne diseases, but also products that may be considered processed or produced in an unethical or hazardous method for the environment. For example, the linkage between the BSE (Bovin Spongiform Encephalopati) in beef and CJD (Creutzfeld-Jakobs Disease) in humans changed the consumption pattern rapidly in Europe, although not all countries reported occurrence of BSE. Consequently, these issues create incentives for the agribusiness firm to design programs for differentiating food products on basis of the perceived quality aspects. Producers supplying products that appeal to consumers' tastes have incitement to differentiate their products by other means than the pricing mechanism. The differentiation process is carried out through implementation of quality-, or certification programs. Certification programs and organizations like ISO, USDA, FAIRTRADE, CROP-WATCH, PDO, PGI, and Organic Europe, distinguish the product quality in terms of in production process, origin, and other tangible or intangible characteristics. When one or several stages in the food chain join to establish specific quality standards, both producers and consumers might reap economic gains through lowered uncertainty and increased efficiency. On the contrary, there is also a probability that the development of quality programs may further enhance market power, thus offset the potential social gains of the program. In essence, a certification program used by individual stages in the agribusiness chain may lead to vertical or horizontal cooperation (collusion), thus potentially moving away from perfect competition. Marette, Crespi, and Schiavina (1999) observe that agricultural markets are working imperfectly due to asymmetric information, where the consumers lack perfect information about the product quality. The suppliers, on the other hand, have incentives to produce both high and low quality products, although the consumers always prefer the higher quality products. The authors hypothesize that the societal welfare increases if consumers can distinguish between high quality and low quality products. Marette et al test this hypothesis by developing a partial equilibrium model under imperfect information in two elaborate scenarios. The model derived by Marette et al treats labeling in agricultural markets in a delicate way. With the certification scheme in place the consumer are able to distinguish between high and low quality products. However, the certification implies that the high quality producers gain market power. The low quality producers are no longer producing, and the high quality producers can exercise market power by either colluding on quantities, e.g. act as a joint monopolist, or play a quantity setting Nash-Cournot game. Essentially, they show that the societal welfare increases when high quality producers come together in a certification scheme and eliminate asymmetric information. Nevertheless, it is crucial to note that the assumptions build in the partial equilibrium framework drives the results. First, the authors choose to use a demand function, which strictly discriminates high quality from low quality products. Second, the authors' assumes that all firms have access to the same technology and have identical marginal cost of production. Third, the certification scheme does not alter the high quality firms' marginal cost. The objective of this study is to analyze certification programs and its impact on the market structure using a programmable mixed complementarity model. This study continues developing the model from Marette et al. Specifically, this study attempts to relief some of the rather restrictive assumptions on consumer and producer behavior that Marette et al have in their paper. First, the results are not stable for perturbations of the quality parameters, and the cost of certification. The results are not invariant to the cost of certification, and for high cost of certification, both producers and consumers are worse off. Second, constructing a utility function that permits demand for low quality products yield rather interesting results as both low quality and high quality producers can coexist under certification. The (aggregate) output level increases with certification. Nevertheless, the prices charged are vastly different between the certified and non-certified product: the high quality products are seven times expensive than the low quality (uncertified) product. Essentially, with certification the consumers' surplus and low quality producers profit decreases, whereas the high quality producers profit increases. The producer profit for high quality producers increases from .02 to .145 units since they produce more units of output to higher price. The low quality producers on the other hand serve the fringe market with relatively small prices, and their profit decreases to .006 units. When there are no high quality producers on the market, the low quality producers supply the whole market. As the high quality producers increase in number, the Nash-Cournot equilibrium approaches the competitive market outcome, i.e. the market price approaches the firm's marginal cost. Hence, as the market price approaches zero, each producer supplies an infinite small unit of output, and the total welfare approaches unity. Nevertheless, with certification, there is a clear trend towards the low quality producers becoming fringe suppliers. The qualitative difference between varying the number of high and low quality firms is that the welfare is increasing in the number of high quality producer, whereas the total welfare impact is ambiguous when varying the number of low quality producer. Hence, there are two aggregate types of consumers: one inelastic and another elastic segment of consumers. The inelastic high quality type has a strictly higher willingness to pay for high quality products. The second type, on the other hand, also likes high quality, but is more sensitive to price changes than the high quality type. The study proposes by in large three major revisions to the model developed by Marette et al. First, instead of using a linear utility function that serves as a linear approximation to any utility function it is deemed appropriate to first a concrete representation of consumer behavior using a second order Taylor-series approximation to consumer demand where consumers' decision parameters include prices for both certified and uncertified products. Second, rather than assuming a zero unit of production, it is deemed appropriate to extend the framework by developing an underlying production technology with associate marginal cost. Third and lastly, the current model setup does not allow low quality producers to supply high quality goods. This is a rather abstract assumption, however, and should be extended to allow producers to interchangeably supply both high and low quality products, based on profit maximizing principles rather than subjectively chosen rules.
Keywords: 330